New Eucalyptus (Myrtaceae) species host of Blastopsylla occidentalis (Hemiptera: Aphalaridae) and its parasitism by Psyllaephagus blastopsyllae (Hymenoptera: Encyrtidae) in Indonesia: Species Eucalyptus (Myrtaceae) baru yang menjadi inang Blastopsylla occidentalis (Hemiptera: Aphalaridae) dan parasitismenya oleh Psyllaephagus blastopsylla (Hymenoptera: Encyrtidae) di Indonesia - de Souza Tavares, Wagner; Listyaningrum, Wahyu; Yuwono Suprianto, Eko; Pranata Saragih, Muhammad Iboy; Siahaan, Shanavina; Santhakumar; Tarigan, Marthin; Duran, Alvaro (Jurnal Entomologi Indonesia, 2024)
Blastopsylla occidentalis Taylor (Hemiptera: Aphalaridae), native to Australia, causes damage to an increasing number of Eucalyptus (Myrtaceae) species and their hybrids in a growing number of countries. This is partly because predatory insects and spiders have low potential to reduce B. occidentalis populations. The purpose of this study was to report a new host of B. occidentalis and the parasitism of this insect by Psyllaephagus blastopsyllae Tamesse, Soufo, Tchanatame, Dzokou, Gumovsky, & Coninck (Hymenoptera: Encyrtidae) in Indonesia. Blastopsylla occidentalis nymphs parasitized were collected from five Eucalyptus pellita F. Muell. trees on October 3rd, 2023, in Senoni, East Kalimantan, Indonesia, and reared in a laboratory until their adults or P. blastopsyllae emerged. The adults recovered from this parasitoid were identified by morphological analysis of their bodies. Eucalyptus pellita is a new host for B. occidentalis. This is the first time in Asia (Indonesia) that P. blastopsyllae has been reported. This new insect-host association alerts the world to the need to develop management strategies for B. occidentalis on E. pellita plantations. The recovery of P. blastopsyllae also opens up new perspectives for the development of biological control programs in Indonesia.